The Embracing workplace flexibility: will virtual meeting technology remain successful during post Covid-19 pandemic? - Marbun, Imam Asma Nur Alam (Jurnal Studi Komunikasi, 2023)
The Covid-19 pandemic has created a big impact on the way people work in nearly all countries around the world, that is the increasing use of video conferencing technology devices to run virtual meetings. Virtual meeting technology such as Zoom has been be labelled by many as a technology that was successfully adopted globally in the pandemic era. Using the combination of Van Loon's enframing/binding-use model with the restrictive effect on the use of technology from Neil Postman, this study is aimed to determine whether or not virtual meeting technology can be classified as successful technology, during and after the pandemic. By using literature review on a number of international and domestic scientific literatures supported by relevant datasets, this study concluded that the covid-19 pandemic has formed virtual meeting applications a successful technology due to its ability in maximizing the potential of enframing its utilities, binding users through habituation, and providing restrictions on the use of other alternatives. This study also found that in the future, hybrid work patterns are predicted to be the choice of many companies which makes virtual meeting devices will remain a successful technology both now and in the future.